PEMBELAJARAN EDUTAIMENT DENGAN SULAP SUARA BONEKA DI RA AL-QUR’AN IQRO PEMATANGSIANTAR - Ahmad Ichsan Yafi Hutagalung; Dewi Juniarti (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini (PGPAUD), 2022)
This research aimedto determine edutainment learning with puppet voice magic at RA A-Ql ur'an Iqro Pematangsiantar. This research is packaged with qualitative research methods, with data collected using active participation observation techniques, sem-sitructured interviews, and documentation. After data collection, then proceed with data analysis by reducing adta, presenting data, and verifying data.The results of this study indicate that the magic of the voice of the doll that makes the doll speak for itself will provide fun learning for early childhood because it still has a strong enough imagination poweTrh. e benefits obtained such as being able to encourage children to come to school, develop children's courage, and also develop children's communication skills